Meeting report of the STAR—Sensitization in Transplantation Assessment of Risk: Naïve Abdominal Transplant Organ subgroup focus on kidney transplantation. Issue 9 (3rd August 2018) - Mannon, Roslyn B.; Askar, Medhat; Jackson, Annette M.; Newell, Kenneth; Mengel, Michael
Abstract : The development of de novo donor‐specific HLA antibody (dnDSA) is a critical feature contributing to late allograft failure. The complexity of the issue is further complicated by organ‐specific differences, detection techniques, reliance of tissue histopathology and changing diagnostic criteria, ineffective therapies, and lack of consensus. To tackle these issues, the Sensitization in Transplantation Assessment of Risk (STAR) 2017 was initiated as a collaboration of the American Society of Transplantation and American Society of Histocompatibility and Immunogenetics consisting of 8 working groups with the goal to provide guidelines on how to assess risk and risk stratify patients based on their potential alloimmune and DSA status. Herein is a summary of discussions by the Naïve Abdominal Working Group, highlighting currently available data and identifying gaps in our knowledge on the development and impact of dnDSA following kidney transplantation. Abstract : The authors report the proceedings of the naïve kidney working group of the ASHI‐AST STAR initiative identifying the development of de novo donor‐specific HLA antibody following kidney transplantation.